REVOLUTIONIZING JUSTICE: LAW ENFORCEMENT THROUGH THE LENS OF PROGRESSIVE LAW - Musmuliadin, Musmuliadin; Indarti, Erlyn; Rochaeti, Nur (UI Scholars Hub, 2024)
When government functions must be carried out and cannot be halted, even if the law does not clearly or completely regulate them, the role of discretionary authority (discretion) becomes crucial. This is particularly evident in the discretionary authority held by the Indonesian National Police, which is essential both for the police themselves and in the execution of their duties in conducting investigations and prosecutions. This study focuses on the application and implementation of discretion by the police in conducting investigations and prosecutions, and how a progressive legal framework can revolutionize the pursuit of justice. By employing a qualitative analysis and the constructivism paradigm, this research explores how law enforcement officers understand and apply their discretionary powers. It also examines the implications of these practices for achieving justice within society. The findings reveal that police discretion is inherently intertwined with the identity of the police, both as individuals and as an organization. The use of this authority is pivotal in ensuring that law enforcement officers perform their duties effectively, not only to promote good governance but also to foster justice within the community. Justice, as a fundamental value in human life, remains a complex and multifaceted issue. Various interpretations of justice lead to diverse perceptions among individuals and groups, influenced by their knowledge and experiences. Therefore, it is essential to recognize that 'justice will be understood differently according to the paradigm adopted. By adopting a progressive legal lens, this study highlights the potential for transformative changes in law enforcement practices, ultimately contributing to a more just and equitable society